Physical protection of soil organic matter following mechanized forest operations in Pinus radiata D.Don plantations - Gartzia-Bengoetxea, Nahia; Arbestain, Marta Camps; Mandiola, Ekhi; Martínez de Arano, Inazio (Soil biology & biochemistry, 2011)
Mechanized forest operations have a large impact on soil systems, and may cause disruption of aggregates and exposure of previously protected soil organic matter to microbial attack. In this study, we investigated how C storage, soil structure and unprotected, physically protected and resistant C pools recover 0, 7 and 20 years after mechanical harvesting and site preparation in second rotation Pinus radiata D.Don plantations. We detected differences in dry mean weight diameter (DMWD) of aggregates, with higher DMWD in 0- and 7-year-old pine stands (8.7 and 7.5 mm, respectively) than in 20-year-old stands (4.1 mm). This was attributed to the compaction induced by heavy machinery, as reflected by the positive relationship between DMWD and bulk density ( r = 0.85, P < 0.05). Organic C contents in the top 5 cm were similar 0 and 7 years after disturbance, but were twice as high after 20 years, with mean values of 25, 28 and 52 Mg C ha −1, respectively. In addition, the resistant C pool was also reduced by up to 7% after clearance. In contrast, unprotected C and physically-protected C were greatest in the youngest stands, indicating that stand establishment and harvesting with heavy machinery may have broken soil aggregates and exposed the previously protected SOM to microbial decomposition and that forest operations may create new mega-aggregates able to protect organic residues. However, the lowest physically-protected C values in 20-year-old pine stands may also be attributed to differences in SOM quality. The alkyl C/O-alkyl C ratios were highest in the oldest stands, indicating that SOM in these stands was more resistant to further decomposition. Mechanized forest operations in radiata pine stands released at least 30 t C ha −1 from the first 5 cm of the soil profile immediately after clearance, caused significant alterations in the soil structure, which lasted for a minimum of seven years, and also reduced the resistant C pool. As the Kyoto Protocol encourages forest management practices that potentially increase carbon sequestration, mechanical harvesting and site preparation in these steep slopes should be reconsidered.